Analisis Yuridis Perjanjian Kerja Waktu Tertentu Berdasarkan Pasal 8 Ayat (1) Peraturan Pemerintah Nomor 35 Tahun 2021 Tentang Perjanjian Kerja Waktu Tertentu, Alih Daya, Waktu Kerja dan Waktu Istirahat, dan Pemutusan Hubungan Kerja - Putri, Karladian; Fauziyah; Ubaidillah, Lutfian (Journal of Contemporary Law Studies, 2023)
Agreement as law for the parties who make it. Indonesia as a rule of law country, reflects every behavior of society based on positive law in Indonesia. The work agreement can be terminated because the rights and obligations between the entrepreneur and the worker or laborer must not conflict with company regulations, collective work agreements and other applicable laws and regulations. This has been agreed and signed and cannot be withdrawn or changed except with the agreement of the parties. Apart from that, this also applies in the economic (business) sector, especially for actors involved in agreements with a company. This research aims to find out the interpretation of the Certain Time Work Agreement (PKWT) based on Article 8 Paragraph (1) of Government Regulation Number 35 of 2021 concerning certain time work agreements, outsourcing, work time and rest time, and termination of employment relations. This research uses juridical-normative legal research. The research results show that the PKWT regulations with a maximum period of 3 (three) years have been removed and PKWT workers will be replaced for no more than 5 (five) years. This includes the extension period as regulated in Government Regulations. If a PKWT worker exceeds the specified time period, then by law it will change to an Indefinite Time Work Agreement (PKWTT).